Intellectual Stagnation: Its Causes, Manifestations and Effects - Juma , Miqdad; shehab , Mohmmed (Islamic Sciences Journal, 2023)
This paper is a scientific study of the issue of intellectual stagnation, its causes and effects. The current research has proven that stagnation has a blight that has clear effects that cannot be tolerated, because intellectual stagnation, if it is found in a society, takes it out of the path of progress to the path of backwardness; therefore, the researcher has studied the subject fundamentally on the one hand. The causes that create it, to the effects arising from it, and as we know that something is known only by its effects, and we have found that clear beyond doubt, so researching and diagnosing such matters gives the therapist an accuracy in giving the effective treatment in eliminating extremism, extremism and decadence in society and scientific and intellectual advancement and progress On the path of correct scientific research by which societies are built and nations progress, through stimulating them with lectures that help in the existence of a healthy society that can return again to the ranks of civilization, away from extremism, backwardness and extremism, so Islam came with all these meanings and announced them